Cardiac myosin binding protein C, adrenergic stimulation and cardiac contractility - Ramburan, Amsha; Korkie, Lundi; Moolman-Smook, Johanna C. (SA Heart Journal, 2017)
Myosin binding protein C remained a perplexing although integral component of the sarcomeric thick filament until the discovery that genetic defects in its corresponding gene is a frequent cause of hypertrophic cardiomyopathy. Basic science investigation subsequently revealed that it is one of the most potent regulators of cardiac contractility. Phosphorylation of its N-terminus upon adrenergic stimulation, causes increased order in myosin heads as well as increased ATPase activity, Fmax and Ca2+-sensitivity of contraction, while its dephosphorylation upon cholinergic stimulation or during low flow ischaemia leads to changes in the sarcomeric thick filament that diminish interaction between myosin heads and actin. This dynamic flux in phosphorylation upon adrenergic stimulation is not only crucial to normal cardiac function and structure, but also vital for protection against ischaemic injury. Genetically-driven deficiency or inadequacy in cMyBPC leads to severe cardiac dysfunction and structural changes, including cardiac hypertrophy and dilation, and particularly attenuates the adaptive increase in left ventricular contractility that follows on β-adrenergic stimulation or pressure overload, resulting in decreased systolic function, and reduced cardiac output.